Multimodality imaging of large-vessel vasculitis. Issue 3 (29th November 2022) - Tarkin, Jason M; Gopalan, Deepa
Abstract : Multimodality cardiovascular imaging is an essential component of the clinical management of patients with large-vessel vasculitis (LVV), a chronic, relapsing and remitting inflammatory disease of the aorta and its major branches. Imaging is needed to confirm the initial diagnosis, to survey the extent and severity of arterial involvement, to screen for cardiovascular complications and for subsequent long-term disease monitoring. Indeed, diagnosing LVV can be challenging due to the non-specific nature of the presenting symptoms, which often evoke a broad differential. Identification of disease flares and persistent residual arteritis following conventional treatments for LVV present additional clinical challenges. However, by identifying and tracking arterial inflammation and injury, multimodality imaging can help direct the use of disease-modifying treatments that suppress inflammation and prevent or slow disease progression. Each of the non-invasive imaging modalities can provide unique and complementary information, contributing to different aspects of the overall clinical assessment. This article provides a focused review of the many roles of multimodality imaging in LVV.